Point-of-care Ultrasound Diagnosis of Bilateral Patellar Tendon Rupture - Kathleen Ogle; Sohaib Mandoorah; Matthew Fellin; Hamid Shokoohi; William Probasco; Keith Boniface (Clinical Practice and Cases in Emergency Medicine, 2020)
Musculoskeletal complaints are one cornerstone of urgent issues for which orthopedic and emergency physicians provide care. Ultrasound can be a useful diagnostic tool to help identify musculoskeletal injuries. We describe a case of bilateral patellar tendon rupture that presented after minor trauma, and had the diagnosis confirmed at the bedside by point-of-care ultrasound. Physicians caring for patients with orthopedic injuries should be familiar with the use of ultrasound to diagnose tendon ruptures.